Weaning of L-thyr eaning of L-thyr eaning of L-thyroxine in H xine in Hypothyr ypothyr ypothyroid Patients U atients Using Homoeopathic M omoeopathic Medicines edicines edicines as an A as an Add on Therapy: A S Therapy: A Single Centr ingle Centr ingle C (Advancements in Homeopathic Research, 2022)
Background: Hypothyroidism, an endocrinal disorder which is conventionally treated by the long continued hormone replacement therapy, exhibits itself through various signs and symptoms pertaining to different systems of the body. Besides some adverse effects, the treatment cost of the therapy impels the patients to seek alternative therapy. Objective: To investigate the role of homoeopathic medicines in neuro-endocrinal diseases like Hypothyroidism in reducing the dosage of hormone replacement therapy. Material and Methods:108 patients diagnosed as Hypothyroid categorized as Group A (receiving homoeopathic medicines along with hormone replacement therapy) and Group B (receiving only homoeopathic medicines) were evaluated with respect to BMI (Obesity), Depression, Thyroid assay and reduction in dosage of L-Thyroxine. The study was retrospectively analyzed at a single out patient department during the period between October 2009 and August 2014. Results: Homoeopathic medicines control the depression (t= 0.75) and obesity (t=0.26), well in patients with hypothyroidism. Homoeopathic drug therapy in comparison to as adjunct with hormone replacement therapy works well in control of T3(t=0.36),T4 (t=1.51) and TSH (t=0.15). Conclusion:Homoeopathic medicine employed as primary therapy or adjunct to the conventional medicines can reduce the drug dependency and reduce the dosage of L- thyroxine.
Keywords: Depression; Hypothyroidism; Hormone replacement therapy; Obesity; Thyroid assay